Identificación de áreas prioritarias que requieren procesos de restauración ecológica en el departamento del Meta, Colombia (2025)
The constant growth of anthropogenic pressure on natural resources has caused a high degree of degradation of ecosystems and loss of habitats of various species, which has generated the need to address these problems through the implementation of strategies addressed locally. , departmental, national and even international. In this order of ideas, restoration emerges as an alternative aimed at the recovery of the most affected ecosystems, which is why it is necessary to establish and determine the areas with the highest priority and urgency for the respective allocation of resources.